ANALYSIS OF AGRICULTURE, BOTTOMAL TERMS IN UZBEK LANGUAGE. - Yelmuratova Albina Satmuratovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides a scientifically based analysis of the analysis of terms in the field of agriculture and botany in the Uzbek language and why this analysis is necessary. In particular, the need to study the field as a separate system, as well as the interrelationships of terms in the field with foreign terms were discussed. The relevance of these terms through theoretical studies has been analyzed across sectors.